Optical Imaging of Cancer-Related Proteases Using Near-Infrared Fluorescence Matrix Metalloproteinase-Sensitive and Cathepsin B-Sensitive Probes - Yhee, Ji Young; Kim, Sun Ah; Koo, Heebeom; Son, Sohee; Ryu, Ju Hee; Youn, In-Chan; Choi, Kuiwon; Kwon, Ick Chan; Kim, Kwangmeyung (IVYSPRING INT PUBL, 2012)
Cathepsin B and matrix metalloproteinase (MMP) play key roles in tumor progression by controlled degradation of extracellular matrix. Consequently, these proteases have been attracted in cancer research, and many imaging probes utilizing these proteases have been developed. Our groups developed cathepsin B and MMP imaging nanoprobes based on polymer nanoparticle platform. Both cathepsin B and MMP imaging probes used near-infrared fluorescence (NIRF) dye and dark-quencher to for high sensitivity, and protease-sensitive peptide sequence in each probe authorized high specificity of the probes. We compared the bioactivities of cathepsin B and MMP sensitive probes in cancer-related environments to investigate the biological property of the probes. As a result, cathepsin B probe showed fluorescence recovery after the probe entered the cytoplasm. This property could be useful to evaluate the cytoplasmic targeted delivery by using probe-conjugated nanoparticles in vivo. On the other hand, MMP probe was superior in specificity in vivo and tissue study. This comparative study will provide precise information about peptide-based optical probes, and allow their proper application to cancer diagnosis.
Keywords: CELL; OVEREXPRESSION; EXPRESSION; SURFACE; MMP-13; ANGIOGENESIS; DESIGN